The Efficacy and Safety of Adalimumab in Treating Pediatric Noninfectious Chronic Anterior Uveitis With Peripheral Retinal Vascular Leakage: A Pilot Study - Song, Hang; Zhao, Chan; Xiao, Junyan; Gao, Fei; Li, Donghui; Zhang, Meifen (Frontiers in Medicine, 2022)
Purpose: This study aims to assess the efficacy of adalimumab in alleviating peripheral vascular leakage in pediatric chronic anterior uveitis patients, along with its ability to improve best-corrected visual acuity (BCVA) and inflammation parameters, its efficacy in reducing topical glucocorticosteroids and systemic immunomodulatory therapy (IMT), and its safety profile. Methods: A self-controlled study of pediatric chronic anterior uveitis patients who presented with peripheral retinal vascular leakage on ultra-widefield fluorescein fundus angiography and underwent adalimumab treatment was conducted. The primary outcome was the extent of retinal vascular leakage at the 3-month and 6-month follow-up visits. Secondary outcomes included BCVA, inflammation parameters (fresh keratic precipitates, anterior chamber cell and vitreous cell grades), frequency of topical glucocorticosteroid eyedrops, IMT load and adverse effects at the 3-month and 6-month follow-up visits. Results: Twenty patients with a mean age of 9.30 ± 3.26 years old were included. The mean follow-up period was 9.0 ± 3.0 months, with all patients followed up for at least 6 months. At the 3-month and 6-month follow-ups, the peripheral vascular leakage score decreased significantly (2.87, 95% CI (2.14, 3.60), P<0.001 for 3 months, 2.75, 95% CI (1.76, 3.73), P<0.001 for 6 months). Alongside BCVA (P=0.013 for 3 months, P=0.005 for 6 months) improved significantly, inflammatory parameters represented by fresh keratic precipitates, anterior chamber cell and vitreous cell grades improved significantly (P<0.001, P<0.001, for all parameters) and topical glucocorticosteroids usage was significantly reduced (P<0.001, P<0.001) at 3 months and 6 months. There was also a statistically significant reduction in systemic IMT load at 6 months (P<0.001). Adverse events in the observation period included local redness around the injection site and mild upper respiratory symptoms. Conclusion: Adalimumab could effectively alleviate peripheral vascular leakage in pediatric patients with chronic anterior uveitis. It could also be helpful in improving BCVA and inflammation parameters and decreasing topical glucocorticosteroid eyedrops and systemic IMT. Adalimumab is generally safe for pediatric uveitis.